Neritic tintinnid community structure and mixing with oceanic tintinnids in shelf waters of the Pacific Arctic Region during summer. (15th April 2022) - Wang, Chaofeng; Xu, Zhiqiang; He, Yan; Yuan, Chao; Li, Haibo; Zhao, Yuan; Denis, Michel; Zhang, Wuchang; Xiao, Tian
Abstract: Tintinnids play an important role in the microbial food web and consist of neritic and oceanic ones biogeographically. Neritic tintinnid species are mainly present in continental shelf areas. Knowing their community structure is thus critical to better understand the ecological function of microzooplankton in the Pacific Arctic Region. During the summer of 2019, neritic tintinnid diversity, vertical distribution, and mixing with oceanic tintinnids were investigated from the Bering Sea to the Chukchi Sea. A total of 19 neritic tintinnid species belonging to 5 genera were identified. All of the neritic species were reported in waters south of the Pacific Arctic Region. No endemic Arctic neritic tintinnid was found. The distributions of nine abundant neritic species exhibited no difference between the Bering Sea and Chukchi Sea. Abundant neritic species were divided into surface- and bottom-dwellers according to their vertical distributions. Bering Shelf Water was dominated by neritic bottom-dwellers, while Anadyr Water was inhabited by neritic surface-dwellers. Neritic and oceanic tintinnids from the Pacific were mainly advected into the Chukchi Sea by Bering Shelf Water. Neritic bottom-dwellers could be mixed into surface waters possibly due to upwelling caused by Pacific Inflow Water flow over shelves. In surface waters, the neritic tintinnid community represented <50% of the total tintinnid abundance. Our results will help to predict future changes in the microzooplankton community under the influence of global warming and increasing Pacific Inflow Water on the Pacific Arctic Region shelf as well as in the Arctic basin. Highlights: Nine abundant neritic species were divided into surface- and bottom-dwellers according to vertical distribution, and exhibited no distribution difference between Bering Sea and Chukchi Sea. Bering Shelf Water (BSW, salinity ranged from 31.8 to 32.5) was dominated by neritic bottom-dwellers, while Anadyr Water (AW, salinity >32.5) was inhabited by neritic surface-dwellers. Neritic tintinnid community represented <50% of total tintinnid abundance in surface waters. Neritic and Oceanic tintinnids from Pacific were mainly advected into the Chukchi Sea by BSW. The BSW might be the main channel for transporting Pacific microzooplankton into Arctic Ocean.